Strictly Drawings : 20th Century Masters. (New York : Helen Serger, la boetie, inc., 1985)
Balthus Baumeister ; Boccioni ; Bonnard ; Botero dubuffet ; Feininger ; Grosz ; Hoelzel ; Kirchner ; Klee ; Klimt ; Kubin ; Léger ; Malevich ; Matisse ; Meidner ; Miro ; Modersohn-Becker ; etc.
Strictly Drawings : 20th Century Masters, Helen Serger, la boetie, inc., New York in Collaboration with Kunsthandel Wolfgang Werner KG, Bremen, October - December 1985
Engels
boek